A preliminary comparative perspective on the role of multinational enterprises in influencing labour relations of their host nation - OLABIYI, OLANIYI JOSHUA (Advances in Social Sciences Research Journal, 2020)
This paper examines the operations of multinational enterprises (MNEs) in so far as they are able to influence the public and labour relations policy and law of their host nation with a special attention on African nations. It is to be expected that MNEs would already be comfortable with the mechanisms in place for the resolution of labour-related or commercial disputes in their country of origin. The question then that arises is: If confronted with an employment relations situation in their host nation, would the MNE attempt to circumvent or adapt the process to suit what they are already familiar with? This could pose a challenge for the practice of international labour law. Literature (Briscoe, Schuler & Tarique, 2012; Eweje, 2009; Iyanda & Bello, 1979; Onimode, 1978) already alludes to the fact that MNEs tend to take the ‘line of least resistance’ if confronted with ‘higher’ labour standards. A comparative exploratory analysis was undertaken. The paper identified MNEs in selected African countries – Nigeria, South Africa, and Zambia – that have been reported to have had a challenge in dealing with labour-related or commercial standards of their host nation. The selected MNEs had been reported in the news media for having had a ‘run in’ with their host nation on, at least, a labour - or commercial law-related matter. The principal legislation governing labour relations in these countries are, in some cases, briefly highlighted to underscore the extent of their breach or disregard by the examined MNEs. Furthermore, a qualitative, thematic analysis of selected reported cases involving these MNEs were undertaken to highlight evidences (or instances) of attempts, if any, by the MNEs to circumvent the commercial, fiscal or labour standards of the host nation. Finally, it is hoped that the result of the above analyses would inform the possibility of proposing a framework for MNEs compliance with the labour standards of their host nation.